Clean and Healthy Behavior in Efforts to Prevent Covid-19 Against Communities Padang Bulan Neighborhoods - hamrin, Muhammad Husni T; Nasution, Faiz Albar (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic caused some countries in the world to become restless, because the virus is still very new and various parties still do not understand how to handle it. The problem of Covid-19 is often caused by a lack of awareness of the community's environment to health protocols. Therefore, education related to clean and healthy living behaviors should be really socialized to the community. One of the areas in Medan that is the target of this busker is Padang Bulan Village. As for the results of socialization activities showed, First socialization material that has been presented by the dedication team is very easy to understand the participants of the activity. Second, the participants realized that the problem of the Covid-19 pandemic was a joint responsibility. Third, the participants are willing to form a team of volunteers in each padang bulan environment to socialize to other communities on clean and healthy living behaviors.